2017
DOI: 10.3892/etm.2017.5379
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of MPR-CTU combined with precise intraoperative ultrasonography guided flexible ureteroscope in the treatment of renal cystic disease

Abstract: The safety and efficacy of multi-planar reconstruction (MPR) image post-processing technique-computed tomography (CT) urography (CTU) combined with precise intraoperative ultrasonography guided flexible ureteroscope in renal cyst incision and drainage in the treatment of cystic diseases of kidney were evaluated. A total of 68 patients were randomly divided into control and observation group (n=34). All the patients were treated with renal cyst incision and drainage under flexible ureteroscope. The control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A recent Chinese randomized controlled trial confirmed that the injection of methylene blue into the parapelvic renal cysts reduced the identification time and operation time of the cysts under a flexible ureteroscope (21). A previous study revealed that MPR-CTU combined with a precise intraoperative ultrasonography-guided flexible ureteroscope exerted better therapeutic effects (increased the successful rate of surgery and reduced complications) via easily locating the cystic wall compared with the flexible ureteroscope technique (5).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent Chinese randomized controlled trial confirmed that the injection of methylene blue into the parapelvic renal cysts reduced the identification time and operation time of the cysts under a flexible ureteroscope (21). A previous study revealed that MPR-CTU combined with a precise intraoperative ultrasonography-guided flexible ureteroscope exerted better therapeutic effects (increased the successful rate of surgery and reduced complications) via easily locating the cystic wall compared with the flexible ureteroscope technique (5).…”
Section: Discussionmentioning
confidence: 98%
“…Holmium lasers are commonly used for the incision and drainage of parapelvic renal cysts under a flexible ureteroscope (5,14,22). Yu et al (14) used a holmium laser to incise and drain endogenous symptomatic renal cystic diseases under a flexible ureteroscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic renal cyst removal and decompression have advantages for abducted renal cysts, but for endogenous renal cysts, the operation is di cult, the window range is small, the trauma is large, and the operation time is long. In recent years, with the development of ureteroscopy technology, exible ureteroscopy combined with holmium laser surgery has advantages for the treatment of endogenous renal cysts and is widely used in clinical practice [4]. However, patients with renal cysts and kidney stones are rare.…”
mentioning
confidence: 99%